Relationship between Thyroid Autoimmunity and Depression, Quality of Life, and Disease Symptoms in Patients with Fibromyalgia and Rheumatoid Arthritis - Bedriye Mermerci Başkan,; Filiz Sivas,; Lale Akbulut Aktekin,; Fatma Gül Yurdakul,; Nilay Kılıç Çınar,; Hatice Bodur,; Kürşat Özoran, (Archives of Rheumatology, 2010)
Objective: The aim of this study was to evaluate the presence of thyroid autoantibodies in patients with fibromyalgia (FM) and rheumatoid arthritis (RA) and to investigate the relationship of these antibodies with depression, quality of life, and disease symptoms. Materials and Methods: Sixty-five patients with FM, 39 patients with RA, and 40 healthy controls were included in the study. Serumfree thyroxine, free triiodothyronine, thyrotropin, and anti-thyroglobulin (TgAb) and anti-thyroid peroxidase antibodies (TPOAb) were measured by immunometric assay. Sociodemographic characteristics, alcohol use, smoking status, morning stiffness, number of joints affected by pain, and presence of accompanying symptoms were recorded. All patients were questioned about the severity of pain, sleep disturbances, fatigue, and morning fatigue. The Fibromyalgia Impact Questionnaire (FIQ) was used to evaluate the quality of life and Beck Depression Inventory (BDI) was used to evaluate the presence of depression. Results: The rates of TPOAb and TgAb positivity were 13.8% and 15.4%, 2.6% and 5.1%, and 5.0% and 5.0% in the FM, RA, and control groups, respectively; there was no significant difference between the groups. Thyroid autoimmunity was noted in 18.5%, 5.1%, and 7.5% of the patients in the FM, RA, and control groups, respectively; there was no significant difference between these groups. There were significant differences between the groups with respect to widespread pain, sleep disturbances, fatigue, and morning fatigue evaluated by VAS and the mean FIQ and BDI scores; the highest values were noted in the FM group. Significantly higher ESR, CRP and TSH levels, and proportion of postmenopausal women were noted in FM patients with thyroid autoimmunity compared to FM patients without thyroid autoimmunity. No significant difference existed between RA patients with or without thyroid autoimmunity. Conclusion: No significant differences existed between FM patients, RA patients, and healthy controls in terms of thyroid autoimmunity. We suggest that there is no association between thyroid autoimmunity and quality of life, severity and frequency of accompanying symptoms, and presence of depression in patients with FM and RA. (Turk J Rheumatol 2010; 25: 130-6)